Role of the Hedgehog pathway in the pancreatic tumour microenvironment - Saini, Francesca (2014)
Pancreatic cancer is a solid tumour with poor prognosis and ineffective therapeutic approaches. The role of the tumour microenvironment in supporting pancreatic tumour growth and metastasis has been demonstrated. In particular, a new concept of the stem cell niche as a mixed population of mesenchymal stem cells and niche cells (myofibroblast cells) involved in promoting these processes is emerging. Paracrine transmission of the Hedgehog (Hh) pathway in the pancreatic tumour microenvironment has previously been reported.